Nationalism, Language, and Muslim Exceptionalism: By Tristan James Mabry (Philadelphia: University of Pennsylvania Press, 2015. 254 pages.) (American Journal of Islam and Society, 2017)
Tristan James Mabry’s research investigates whether Muslim populationsare exceptionally resistant to ethnonationalism, which he assumes to be moreconducive to a liberal democratic form of government than any concept ofcommunity defined in terms of a shared religion. He concludes that Muslimsare not immune to it, and that the determining factor in whether a Muslimcommunity will organize itself according to ethnonationalism instead of Islamism– Mabry apparently considers these the only modes worth mentioning– is whether they develop a print culture in their local vernacular.Ultimately, the author concludes that nationalism founded upon ethnic solidarityis inherently superior to alternative sociopolitical models, and thereforeadvocates promoting local ethnonationalisms as a strategy to preventMuslims from organizing themselves in terms of shared religious identity(p. 202) ...